Aerosol single-scattering albedo retrieval over North Africa using critical reflectance - Wells, Kelley Carlene, author; Kreidenweis, Sonia M., advisor; Stephens, Graeme L., 1952-, committee member; Remer, Lorraine Ann, committee member; Collett, Jeffrey L., committee member; Peel, Jennifer L., committee member (Colorado State University. Libraries, 2010)
The sign and magnitude of the aerosol radiative forcing over bright surfaces is highly dependent on the absorbing properties of the aerosol. Thus, the determination of aerosol forcing over desert regions requires accurate information about the aerosol single-scattering albedo (SSA). However, the brightness of desert surfaces complicates the retrieval of aerosol optical properties using passive space-based measurements. The aerosol critical reflectance is one parameter that can be used to relate top-of-atmosphere (TOA) reflectance changes over land to the aerosol absorption properties, without knowledge of the underlying surface properties or aerosol loading. Physically, the parameter represents the TOA reflectance at which increased aerosol scattering due to increased aerosol loading is balanced by increased absorption of the surface contribution to the TOA reflectance. It can be derived by comparing two satellite images with different aerosol loading, assuming that the surface reflectance and background aerosol are similar between the two days. In this work, we explore the utility of the critical reflectance method for routine monitoring of spectral aerosol absorption from space over North Africa, a region that is predominantly impacted by absorbing dust and biomass burning aerosol. We derive the critical reflectance from Moderate Resolution Spectroradiometer (MODIS) Level 1B reflectances in the vicinity of two Aerosol Robotic Network (AERONET) stations: Tamanrasset, a site in the Algerian Sahara, and Banizoumbou, a Sahelian site in Niger. We examine the sensitivity of the critical reflectance parameter to aerosol physical and optical properties, as well as solar and viewing geometry, using the Santa Barbara DISORT Radiative Transfer (SBDART) model, and apply our findings to retrieve SSA from the MODIS critical reflectance values. We compare our results to AERONET-retrieved estimates, as well as to measurements of the TOA albedo and surface fluxes from the Geostationary Earth Radiation Budget (GERB) experiment, Atmospheric Radiation Measurement (ARM) program, and Clouds and the Earth's Radiant Energy System (CERES) data. Spectral SSA values retrieved at Banizoumbou result in TOA forcing estimates that agree with CERES measurements within ± 5 W m-2 for dusty conditions; however, the retrieved SSA translates to a much larger positive TOA forcing than CERES in the presence of dust-biomass burning mixtures. At Tamanrasset, the retrieval captures changes in aerosol absorption from day to day, but the SSA appears to be biased high when compared to AERONET and CERES. This may be due to the higher surface reflectance in this region, an overestimation of the dust aerosol size, or changing background aerosol between the clean and polluted day. Our retrieval results indicate that we can be most confident in the retrieved SSA for scattering angles between 120° and 160°, satellite view angles less than ~45°, and in cases when the background aerosol on the cleaner day is non-absorbing.
Keywords: remote sensing; radiative forcing; dust; biomass burning; aerosol absorption; Atmospheric aerosols -- North Africa -- Remote sensing; Artificial satellites in remote sensing -- North Africa; Albedo -- Remote sensing; Biomass -- Combustion -- North Africa